Anne Waldschmidt, Hanjo Berressem y Moritz Ingwersen (eds.) (2017): Culture - Theory - Disability: Encounters between Disability Studies and Cultural Studies. Bielefeld: Transcript Verlag - María Esther Pérez Dalmeda (Revista Española de Discapacidad, 2017)
Reseña de la obra 'Culture - Theory - Disability: Encounters between Disability Studies and Cultural Studies' (2017) de Anne Waldschmidt, Hanjo Berressem y Moritz Ingwersen (eds.).